Recognizing the Batik Heritage of the Archipelago: From Coastal to Inland - Syafitri, Musdalifah (Professorline, 2025)
Batik is an Indonesian cultural heritage that has been recognized by UNESCO as an Intangible Cultural Heritage. This article reviews the diversity of the archipelago's batik, from coastal to inland areas. The discussion begins with the history of batik development in Indonesia, including the influence of various cultures such as Chinese, Indian, Arabic and European. Next, the article discusses the distinctive characteristics of coastal batik, which is generally brightly colored with flora and fauna motifs, and inland batik, which tends to use dark colors with geometric motifs. The differences in philosophy, manufacturing techniques, and materials used in coastal and inland batik are also described. The article also highlights some famous batik centers such as Pekalongan, Cirebon, Lasem, Yogyakarta, and Solo, and explains the characteristics of each. Efforts to preserve and develop batik as a cultural heritage and creative economic potential are also discussed. By reviewing the richness of the archipelago's batik, this article aims to increase public appreciation of Indonesia's cultural heritage and encourage preservation and innovation in the art of batik.